Plasma and cell lysate proteins associated with treatment outcome in acute myeloid leukaemia - Barantalab, Fatemeh; Chong, Pei Pei; Lee, Cindee; Yiau, Stephnie Kang Xian; Chang, Kian Meng; Seman, Zainina; Abdullah, Maha (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Drug-resistance is a major hindrance to successful treatment of AML. Current predictive biomarkers are mainly genetic aberrations and insufficient in foretelling treatment outcome in all acute myeloid leukaemia (AML) due to its heterogeneous and aggressive nature. Proteins are stable and reliable. Secreted proteins in AML may have predictive or prognostic values for early intervention. Proteomic studies on AML are few and further investigations will benefit in selection of best markers. The aim of the study was to identify differentially expressed plasma proteins in AML with different treatment outcome. Methods: Two-dimensional electrophoresis (2-DE) technique was utilised to identify proteins differentially expressed in chemo-sensitive/chemo-resistant AML. Plasma and peripheral blood mononuclear cell (PBMC) lysate proteome analysis were performed on six chemo-resistant, four chemo-sensitive and six healthy controls and seven chemo-resistant, three chemo-sensitive and six healthy controls, respectively. Each experiment was conducted in duplicate or triplicate. Images were captured and protein spots detected by software. Differentially expressed protein spots were excised from gel and proteins were identified using LC/MS/MS. Proteins spots that were also detected in healthy controls were excluded. Results: Comparing mean % volume of each spot demonstrated significantly enhanced expression of apoliprotein-E (APO-E) and haptoglobin (HP) (p<0.05) in plasma and HNRNP H1 (p=0.049) in cell lysate of chemo-sensitive group. Serotransferrin (STF) from plasma and DNA-PK from cell lysate (p=0.01) were associated with chemo-resistance. Conclusion: This preliminary study identified sever-al potential predictive biomarkers associated with chemo-resistance/chemo-sensitivity to treatment in AML. Further studies with a larger number of samples are required to validate the results.